The representation of female beauty in the Instagram pageant lovers - Syarifudin, Achmad; Ummah, Kuntum Chairum (C-DISC, 2023)
The representation of female beauty in the beauty queen event is only associated with brain, beauty and behavior. Women are not only considered beautiful from the outside, but also need inner beauty through the beauty queen event. Pageant lovers as loyal supporters of the beauty queen event also represent female beauty through Instagram accounts, in addition to raising support and updating information about beauty pageants. This study aims to describe women's beauty represented by Instagram pageant lovers on social media. The research method uses the semiotic approach of Roland Barthes on Instagram accounts of pageant lovers, including @portalpageant.id, @pageantcrownwarriors, and @indopageant. The time span of the analyzed uploads was January to February 2023. The results showed that the representation of female beauty on the accounts of pageant enthusiasts contains a number of issues, namely that the standard of female beauty is relative with the caption Black Beauty. The issue of commercialization of women through the beauty pageant event can be seen from the disappointment of pageant lovers with the transfer of the license of the Puteri Indonesia Foundation (YPI) and the Miss Universe Philippines fundraiser.